Active Comb Filter Using Operational Transconductance Amplifier. (22nd May 2014) - Ranjan, Rajeev Kumar; Yalla, Surya Prasanna; Sorya, Shubham; Paul, Sajal K.
Abstract : A new approach for the design of an active comb filter is proposed to remove the selected frequencies of various signals. The proposed filter is based on only OTAs and capacitors, hence suitable for monolithic integrated circuit implementation. The workability of the circuit is tested using PSPICE for test signals of 60, 180, 300, and 420 Hz as in ECG signal. The results are given in the paper and found to agree well with theory.